Persepsi Guru Terhadap Kepemimpinan Pembelajaran Kepala Sekolah Dilihat dariPerbedaan Gender di Provinsi Kalimantan Selatan - Zaenal Fanani (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2019)
This research was aimed at obtaining a picture of teacher’s perception of their school principals’ instructional leadership and the impact gender might has on those perceptions. The Assessment Instrument of Instructional Leardership by Fanani (2013) was used to collect data from 120 teachers who attanding the principal candidate training for measuring teacher’s perception of their school principals’ instructional leadership in 3 districts in South Kalimantan. The main results suggensted at a good category in the four dimensions of instructional leadership. The lowest rated dimension was supervising instruction whereas the highest rated dimension was developing learning vision. There were significant different in the rated learning vision dimension based on gender in favor of female teachers.. This research result contributes to dicision making in developing the school principals’ capacity in conducting instructional leardership.